2021
DOI: 10.3390/foods10112763
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Frozen Fillets of Semi-Dried Gourami Fish (Trichogaster pectoralis) by Using Sorbitol and Citric Acid

Abstract: Semi-dried gourami fish (Trichogaster pectoralis) is popularly consumed domestically and exported as a frozen product. This study was conducted to prevent deterioration quality in frozen fish fillets during storage. This research aims to investigate the effects of sorbitol and citric acid at concentrations of 2.5% and 5% (w/w) of frozen gourami fish fillets compared to the fillets soaked in distilled water on physicochemical properties, such as cooking loss, cooking yield, drip loss, pH, TBARS, color, and text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…The mean PV in the present study indicated that COSP treatments may retard the production of initial lipid oxidation products in shrimp. These results were had the same trends with those of chitosan–gelatin coatings film, effective in retarding lipid oxidation in trout fillets [ 18 , 19 ]. COSP might be a good barrier to oxygen permeation and act as a resistant layer between the shrimp surface and its surrounding environment, thus decreasing the diffusion of oxygen to shrimp muscle.…”
Section: Resultssupporting
confidence: 56%
“…The mean PV in the present study indicated that COSP treatments may retard the production of initial lipid oxidation products in shrimp. These results were had the same trends with those of chitosan–gelatin coatings film, effective in retarding lipid oxidation in trout fillets [ 18 , 19 ]. COSP might be a good barrier to oxygen permeation and act as a resistant layer between the shrimp surface and its surrounding environment, thus decreasing the diffusion of oxygen to shrimp muscle.…”
Section: Resultssupporting
confidence: 56%
“…The addition of pepsin, rosemary oil, and citric acid, in the present study, significantly increases the protein and moisture content of the treated fish fillet owing to the proteolytic effect of pepsin (Table 2) and their low pH values (Table 5), subsequently increasing protein dissolution and decreasing water-binding ability. Our findings regarding the effect of citric acid on the chemical composition of basa fish fillets are in harmony with those demonstrated by Klinmalai et al [10], who observed a significant increase in protein content of frozen fish fillets treated with 2% and 5% citric acid. Similarly, Emir Çoban and Özpolat [49] found that rosemary extract had no substantial effect on the moisture content of fish fillets.…”
Section: Proximate Compositional Analysis Of Basa Fish Filletssupporting
confidence: 92%
“…Regarding the decrease in the pH value in citric acid-treated samples, similar results were reported by Klinmalai et al [10], who noticed that treatment of frozen fish fillets with citric acid resulted in a significant decrease in pH (4.51-5.56) values. Moreover, the pH value of the tilapia surimi was significantly decreased with increasing pepsin concentration, which may be due to the low pH (2.5) value of pepsin [33].…”
Section: Ph and Total Volatile Base Nitrogen (Tvbn) Of Basa Fish Filletssupporting
confidence: 86%
See 1 more Smart Citation
“…Snakeskin gourami (Trichogaster pectoralis) is one of the most important freshwater fsh commonly cultured in Southeast Asia, including Laos, Vietnam, Cambodia, Malaysia, Indonesia, and Tailand [1][2][3][4]. Snakeskin gourami can tolerate a wide range of farming conditions as they have a special breathing organ, the labyrinth, which allows them to exchange oxygen in low oxygen cultivation conditions [5].…”
Section: Introductionmentioning
confidence: 99%